Kritik Ulama Hadits: Ilmu Jarh Wa Ta’dil Sebagai Upaya Dalam Menjaga Orisinalitas Hadits - Hafidz, Abdul (International Conference on Islamic Studies, 2020)
Abstract The critique of the hadith scholars or what is called the science of jarh wa ta'dil is an effort to maintain the originality of the hadith of the Prophet Muhammad. There is a diversity of hadith studies in terms of dlabt, tsiqah, etc, even the emergence of some people who dared to make false hadiths (maudlu') and connect it to Rasulullah SAW. for personal and group interests, the hadith scholars make a strict selection of the hadiths that come to them. Abu Bakr as-Siddiq was the first person to test the authenticity of the hadith in the case of grandmother's inheritance. Likewise, Umar bin Khattab tested the originality of the hadith in the hadith of Abu Musa al-Asy'ari by asking for witnesses. Furthermore, the test of the originality of hadith was carried out by the others Sahabah and the Tabi'in by means of criticism of hadith narrators and discussed their credibility and accountability in order to distinguish between true hadith and false hadith. The peak of jarh wa ta'dil development occurred in the 3rd century H. with the emergence of several Muslim figures who were concerned about the studies of jarh wa ta'dil, such as Yahya bin Ma'in, Ali al-Madini, and others.